A produção do espaço escolar pelos discursos de um grupo de docentes sobre as relações de gênero e sexualidade em Chapecó, Santa Catarina - Durgante, Flávia Rubiane (2018)
The present study approaches the construction of the scholar space through speeches of a group of professors from a public school in Chapecó City, Santa Catarina State, about gender and sexuality issues. The main purpose of this research is to comprehend how gender relations and sexuality make up the scholar space and the way this space is affected by these relations, since scholar space is surrounded by gender relations and, most of the time, these relations are responsible for establishing paradoxes in the school environment. Research-Action (THIOLLENT,1986) was the methodology used in this study that was provided through twelve meetings with the group of professors from the chosen school. Firstly, those meetings were only debates and discussions regarding the subject, then, later, the involved professors started to participate of training moments aiming to reflect and clear their doubts, in accordance with the methodology used in this research. As a way ofinterpreting collected data, it has been used the Discourse Analysis method from the view of Michel Foucault (2009) to analyze collected information in order to comprehend what types of speeches about gender and sexuality were made at school. In doing sothrough speeches, the conclusion is that the school environment is built of two different and paradoxical spaces: the Patriarch space, composed by prejudiced and conservative speeches, and the Deconstruction space, composed by progressive speeches that deconstruct prejudiced speeches. Both spaces, coexisting, make the school environment a paradoxical, relational and open space.(MASSEY, 2009, SILVA, 2014).